CHILD-REARING BARRIERS AND SOCIAL SUPPORT OF MIGRANT FAMILIES : A CASE STUDY OF INDONESIAN MOTHERS LIVING IN SEOUL, SOUTH KOREA - Hati, Getar (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
An increasing number of Indonesian families migrate to South Korea with different social and cultural aspects emerge the challenges in child-rearing. This study examines two purposes related to child-rearing barriers and social support of migrant families by utilizing qualitative research with a case study design. In-depth interviews and observation carried out data collection during August-November 2021 involving six (6) Indonesian migrant mothers living in Seoul using purposive sampling. Mothers were chosen as informants by considering them as the primary caregiver for children. Regarding the first purpose, this study identified internal and external barriers in child-rearing. In addition, three themes related to social support are analyzed, including instrumental support in tangible and service assistance, emotional support related to social adjustment support, and informational support to access services for children. The resources of support systems come from spouses and parents, Indonesian and Korean friends/colleagues, social institutions, and social media networks. Therefore, there is a need for comprehensive social interventions to strengthen social support for migrant families.